An investigation of the effect of maternal depression during pregnancy on maternal and infant hypothalamic-pituitary-adrenal axes - JAIRAJ, CHAITRA (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2018)
Background: Pregnancy is a period of increased vulnerability for developing depression. Several maternal physiological systems, including the hypothalamic-pituitary-adrenal (HPA) axis undergo changes during pregnancy. Studies of the HPA axis in antenatal depression report diverse findings. However, there is strong evidence to suggest that maternal antenatal depression may predispose the offspring to depression in adult life, a foetal programming effect that may be mediated by the HPA axis. The principal aims of this study were to examine the HPA axis in antenatal depression, and investigate for any foetal programming effects of maternal depression during pregnancy on the infant HPA axis. The relationships between maternal early life adversity (ELA) and maternal and infant HPA axes were also explored. Methods: Women were recruited into the study between 20 and 30 weeks gestation, and three groups were compared ? women who were depressed during pregnancy (Depressed), euthymic pregnant women with a prior history of depression (History), and never-depressed pregnant women (Control). Mothers and their infants were then followed up at two and six months postpartum. Saliva samples were collected from mothers and infants at all time points in the study for cortisol quantification. Results and Discussion: The maternal HPA axis during pregnancy was similar in all the three groups studied, with no apparent effect of antenatal depression on diurnal cortisol, total cortisol output, or the cortisol awakening response (CAR). There were no associations between maternal clinical measures during pregnancy and cortisol measures. These findings suggest that the physiological hypercortisolaemia of pregnancy may obscure any depression-driven HPA axis changes. Although there were no effects of antenatal depression on maternal HPA axis during pregnancy, women with a history of ELA had higher evening cortisol levels compared to women with no history of ELA. This effect persisted at both time points postpartum. There is clear evidence in this study for foetal programming of the HPA axis in infants born to women who were depressed during pregnancy. Infants in the Depressed group had higher baseline and post-stressor cortisol levels at six months. Findings from this study suggest that maternal mood and cortisol measures during pregnancy work synergistically with maternal mood and cortisol measures at six months postpartum to influence infant baseline cortisol measures at this time point. Infant post-stressor cortisol levels at six months appear to only be influenced by concurrent maternal cortisol measures. There was no effect of trait depression or maternal early life adversity on infant HPA axis function. Conclusions: Although there were no apparent effects of antenatal depression on the maternal HPA axis, there is clear evidence for foetal programming of the infant HPA axis by maternal depression during pregnancy. The findings in this study highlight the need for further research into the foetal programming effects of maternal depression during pregnancy, in order to reduce illness burden in future generations.
APPROVED
Keywords: HPA axis; Antenatal depression; Foetal programming; Perinatal mental health